(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
When using the liquid defoliant CMD at a rate of 8.0 l/ha, the weight of a piece of cotton was 0.1 g less than in the control. This can be expressed in the harsh and rapid action of the defoliant and the opening of the pods before they are fully ripe due to the drying of the cotton leaves. Based on this point of view, the development of standards for the use of new soft-acting defoliants, taking into account the sharp differences in the properties of defoliants created in recent years, climate change and the mechanization of harvesting operations, is an urgent issue.